Introduction to engineering materials - Murray, G. T. 1927- (Materials engineering, 2008)
Designed for the general engineering student, Introduction to Engineering Materials, Second Edition provides a solid foundation for the nonmaterials major to understand the properties and limitations of materials. Easy to read and understand, the authors use straightforward language to teach the beginning engineer what to look for in a particular material, offer examples of materials usage, and present a balanced view of theory and science alongside the practical and technical applications of material science.